DISCUSSION ON THE TYPES OF LITERARY TRANSLATION IN THE SOVIET TRANSLATION STUDIES - Nathalie R. Neiman (Studia Litterarum)
The article discusses the theory and history of literary translation in the Soviet Union, The article discusses the theory and history of literary translation in the Soviet Union, namely, the dispute between Moscow and St. Petersburg schools of translation. The main focus is on the chapter from an unfinished Doctorate thesis by a Soviet translator and translation studies theorist V.Ye. Shor (1917–1971). The thesis entitled How Many Types of Translation Exist? was turned down by the editors of major academic collections in the field. Shor opposed ideas supported by the school of I. Kashkin though he did it indirectly, by criticizing Vachtin, a scholar who did not belong to the Moscow school of translation. Shor argued against dividing translation into types claiming that the type of translation should be determined by the original. Instead, he proposed a unified univer sal principle that would define the quality criteria of a translation, substantiate the ne cessity of translator’s creativity, and at the same time adequately render ideas and images of the original in the language of translation. This paper shows how fierce discussions between the acolytes of these two schools influenced the decision to reject Shor’s paper that fostered ideas not corresponding with the mainstream lines in translation studies of the 1960-s.